Impact of the Soviet military presence in the Arctic region on Norwegian security policies. - Johnson, Carl E. (Fort Leavenworth, KS : US Army Command and General Staff College, 1990)
This study is an analysis of the security issues in the North Cape region of northern Norway, including the Svalbard Islands and the continental shelf areas of the Barents Sea. It examines the geostrategic significance of the region, the Soviet force structure in the Kola peninsula and the Norwegian defense forces in the Arctic region. The paper then details the current political and economic issues between Norway and the Soviet Union that impact on security in the Arctic. Finally, it examines the Soviet goals and objectives in the North Cape area, and assesses the Norwegian defense policies and NATO reinforcement plans designed to counter Soviet aggression in the Arctic region. The three major research questions address the Soviet view of the threat in the Barents Sea region, the Norwegian reaction to the Soviet threat to the North Cape, and the current status of the NATO capability to respond to a crisis situation in the region. The paper will also examine some of the impacts that Gorbachev's new political policies are having on the region. The study concludes that despite the force reductions in central Europe by both NATO and the Warsaw Pact, the strategic importance of the Barents Sea region, for both security and economic reasons, will keep tensions between Norway and the Soviet Union high in the coming decade. The author postulates that the Soviets will be seeking a cotenancy agreement with the Norwegians for control of the continental shelf area between the North Cape and the Svalbard Islands. Finally, recommendations are made for the upgrade of NATO response capabilities in the Arctic region.